Evans Blue Attachment Enhances Somatostatin Receptor Subtype-2 Imaging and Radiotherapy - Tian, Rui (Theranostics, 2018)
Purpose: Radionuclide therapy directed against tumors that express somatostatin receptors (SSTRs) has proven effective for the treatment of advanced, low- to intermediate-grade neuroendocrine tumors in the clinic. In clinical usage, somatostatin peptide-based analogs, labeled with therapeutic radionuclides, provide an overall response rate of about 30%, despite the high cumulative activity injected per patient. We set out to improve the effectiveness of somatostatin radiotherapy by preparing a chemical analog that would clear more slowly through the urinary tract and, concomitantly, have increased blood circulation half-life and higher targeted accumulation in the tumors. Experimental Design: We conjugated a common, clinically-used SST peptide derivative, DOTA-octreotate, to an Evans blue analog (EB), which reversibly binds to circulating serum albumin. The resulting molecule was used to chelate (86)Y and (90)Y, a diagnostic and a therapeutic radionuclide, respectively. The imaging capabilities and the radiotherapeutic efficacy of the resulting radioligand was evaluated in HCT116/SSTR2, HCT116, and AR42J cell lines that express differing levels of SST2 receptors. Results: The synthesized radiopharmaceutical retained affinity and specificity to SSTR2. The new molecule also retained the high internalization rate of DOTA-octreotate, and therefore, showed significantly higher accumulation in SSTR2-positive tumors. Labeling of our novel EB-octreotate derivative with the therapeutic, pure beta emitter, (90)Y, resulted in improved tumor response and survival rates of mice bearing SSTR2 xenografts and had long term efficacy when compared to DOTA-octreotate itself. Conclusions: The coupling of a targeted peptide, a therapeutic radionuclide, and the EB‑based albumin binding provides for effective treatment of SSTR2-containing tumors.